HUBUNGAN KEPERCAYAAN INDIVIDU DAN EVALUASI TERHADAP KEPERCAYAAN DENGAN NIAT MENIKAH DENGAN LAKI-LAKI PEROKOK PADA MAHASISWI FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS DIPONEGORO - Evitasari Ramadhani; Kusyogo Cahyo; Syamsulhuda BM (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Someone who marries active smokers will definitely be passive smokers. Passive smokers have risks as high as active smokers. College students are in the stage of early adults who are ready for marriage life. This study aims to analyze the intention of Public Health Faculty female students in Diponegoro University to marry smokers. This research was a quantitative research with cross-sectional approach using 1281 female students in Public Health Faculty of Diponegoro University as population which was obtained 98 female students as samples using stratified systematic random sampling technique. Data collection was done through interview with questionnaire. The analytical data were performed univariate and bivariate. Most of them were aged less than 21 years old (60,2%), on their last year of college (53,1%), non smokers (96,9%), didn’t have boyfriend (54,1%), had non smokers boyfriend (60%). Most of them had positive behavioral belief (58,2%) and positive evaluation of belief (60,2%).The results showed that the variables related to behavioral belief (p=0,000) adn evaluation of belief (p=0,000).